2016
DOI: 10.1111/ane.12586
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MEG vs EEG after sleep deprivation in epilepsy

Abstract: MEG as well as EEG-SD are robust long-term predictors for epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Because of its sensitivity for identification of epileptic spikes ( Lin et al, 2003 , Iwasaki et al, 2005 , Kakisaka et al, 2012 ), MEG has been used not only for localization of epileptic sources, but for diagnosis of epilepsy ( Colon et al, 2009 , Duez et al, 2016 , Colon et al, 2017 ), especially when the results of other non-invasive studies have been meager or completely unrevealing. Although the dogma that MEG cannot see radial currents is widespread, less than 5% of the cortical surface is within 15 degrees of radial ( Hillebrand and Barnes, 2002 ).…”
Section: Established Clinical Applicationsmentioning
confidence: 99%
“…Because of its sensitivity for identification of epileptic spikes ( Lin et al, 2003 , Iwasaki et al, 2005 , Kakisaka et al, 2012 ), MEG has been used not only for localization of epileptic sources, but for diagnosis of epilepsy ( Colon et al, 2009 , Duez et al, 2016 , Colon et al, 2017 ), especially when the results of other non-invasive studies have been meager or completely unrevealing. Although the dogma that MEG cannot see radial currents is widespread, less than 5% of the cortical surface is within 15 degrees of radial ( Hillebrand and Barnes, 2002 ).…”
Section: Established Clinical Applicationsmentioning
confidence: 99%
“…For example, a recent study showcased that sleep deprivation EEG (SD-EEG) was a sensitive diagnostic tool for idiopathic generalized but not focal epilepsy 45 . Conversely, a subsequent empirical evaluation revealed that SD-EEG is an efficacious tool for diagnosing epilepsy 46 . These disparities have been attributed to a wide variance in study methodologies 47 .…”
Section: Discussionmentioning
confidence: 99%
“…patient clinic V-EEG PET SPECT NPT SEEG MEG 7T MRI 1 T [29][30][31][32][33][34][35][36][37][38] former had added value. MEG abnormalities are described with FCD [45] and can be used in daily practise [25]. Technical advances are promising and might make MEG more widely available [46].…”
Section: Discussionmentioning
confidence: 99%
“…When an MRI is re-analysed with an a-priori hypothesis more lesions are detected [23,24]. Magnetoencephalography (MEG) is not only a reliable indicator of epilepsy [25] but also a powerful tool to determine a possible epileptogenic focus [26,27] and is of growing presurgical importance in combination with MRI (MRS, magnetic source imaging) [28]. In frontal lobe epilepsy interictal MEG might even be more predictive than ictal semiology in locating the epileptogenic zone [29].…”
Section: Introductionmentioning
confidence: 99%